(untitled) (Journal of Plant Disease Sciences, 2017)
Green synthesis of copper nanoparticles (CuNPs) and its use as antimicrobial activities against plant pathogens is a novel research area. Presently research was undertaken on synthesis of CuNPs from L. leaves Eucalyptus globules as a reducing agent and copper sulphate as precursor. Synthesized copper nanoparticles were characterized by Particles Size Analyzer (PSA) and Atomic Force Microscope (AFM) which showed the size of 30-50 nm. Such confirmed nanoparticles were evaluated against (Loose smut of wheat) Ustilago nuda tritici and (Turcicum leaf blight) by spore germination method Exserohilum turcicum which showed 100 per cent spore inhibition over the control at 50 and 100 ppm respectively. However the synthesized copper nanoparticles were failed to inhibit the mycelial growth of and by poison Sclerotium rolfsii Macrophomina phaseolina food technique. Further, CuNPs did not show any phytotoxicity symptoms on tomato seedlings by spot application on leaves under glasshouse condition.